A history of civilization in Palestine - Macalister, Robert Alexander Stewart (The Cambridge manuals of science and literature, 2011)
Part of the Cambridge Manuals of Science and Literature series, A History of Civilization in Palestine (1912) was written by the scholar and archeologist R. A. S. Macalister. It follows the development of civilization in the region from the time of its earliest inhabitancy till the beginning of the twentieth century.